Clinical and cost implications of using immediate MRI in the management of patients with a suspected scaphoid fracture and negative radiographs results from the SMaRT trial. (August 2019) - Rua, T.; Malhotra, B.; Vijayanathan, S.; Hunter, L.; Peacock, J.; Shearer, J.; Goh, V.; McCrone, P.; Gidwani, S.
Abstract : Aims: The aim of the Scaphoid Magnetic Resonance Imaging in Trauma (SMaRT) trial was to evaluate the clinical and cost implications of using immediate MRI in the acute management of patients with a suspected fracture of the scaphoid with negative radiographs. Patients and Methods: Patients who presented to the emergency department (ED) with a suspected fracture of the scaphoid and negative radiographs were randomized to a control group, who did not undergo further imaging in the ED, or an intervention group, who had an MRI of the wrist as an additional test during the initial ED attendance. Most participants were male (52% control, 61% intervention), with a mean age of 36.2 years (18 to 73) in the control group and 38.2 years (20 to 71) in the intervention group. The primary outcome was total cost impact at three months post-recruitment. Secondary outcomes included total costs at six months, the assessment of clinical findings, diagnostic accuracy, and the participants' self-reported level of satisfaction. Differences in cost were estimated using generalized linear models with gamma errors. Results: The mean cost up to three months post-recruitment per participant was £542.40 (sd £855.20, n = 65) for the control group and £368.40 (sd £338.60, n = 67) for the intervention group, leading to an estimated cost difference of £174 (95% confidence interval (CI) -£30 to £378; p = 0.094). The cost difference per participant increased to £266 (95% CI £3.30 to £528; p = 0.047) at six months. Overall, 6.2% of participants (4/65, control group) and 10.4% of participants (7/67, intervention group) had sustained a fracture of the scaphoid (p = 0.37). In addition, 7.7% of participants (5/65, control group) and 22.4% of participants (15/67, intervention group) had other fractures diagnosed (p = 0.019). The use of MRI was associated with higher diagnostic accuracy both in the diagnosis of a fracture of the scaphoid (100.0% vs 93.8%) and of any other fracture (98.5% vs 84.6%). Conclusion: The use of immediate MRI in the management of participants with a suspected fracture of the scaphoid and negative radiographs led to cost savings while improving the pathway's diagnostic accuracy and patient satisfaction. Cite this article: Bone Joint J 2019;101-B:984–994.